Kepemimpinan Kepala Sekolah dalam Peningkatan Mutu Pendidikan Islam di MTs Salafiyah Wiradesa - Zumzumi, Via Nilna; Ta'rifin, Ahmad; Zumzumi, Vita Nilna; Tranadisa, Sherly Seviola; Aulia, Nurul (IAIN Parepare, 2024)
School principal leadership plays a crucial role in improving the quality of Islamic education at MTs Salafiyah Wiradesa. This study aims to analyze the strategies and actions undertaken by the principal to enhance learning quality. The research uses a qualitative approach with Miles and Huberman data analysis, including data collection through interviews, observations, and documentation, followed by data reduction, presentation, and conclusion drawing. Findings indicate that the principal organizes and assigns teacher duties according to qualifications and certification alignment, fosters a conducive learning environment, optimizes school facilities, and leads structured religious activity programs. This leadership implementation effectively improves learning quality, teacher and student discipline, and overall school management efficiency.